Chapter 1 Doing, talking, and thinking (and why we're not getting it right) - Williams, Clare (Taylor & Francis, 2023)
The way we talk matters. Human thought processes are largely metaphorical, but what happens when our metaphors for law, economy, and society are conceptually inconsistent or inadequate? By taking a deep dive into how we use one metaphor - embeddedness - this chapter shows that if our ways of talking and thinking about legal and economic phenomena are inconsistent, mainstream thoughtways are re-entrenched. At the same time, innovative or imaginative responses to the financial crashes, social crises, and environmental catastrophes facing society can be hidden. This chapter explores our mainstream ways of doing, talking, and thinking about the relationships between law, economy, and society, identifying problematic metaphors and the conceptual heavy lifting they are asked to perform. It also introduces the three personas who guide and ground the conceptual discussion throughout the book.